2021
DOI: 10.1002/agj2.20612
|View full text |Cite
|
Sign up to set email alerts
|

Grazing winter rye cover crop in a cotton no‐till system: Soil strength and runoff

Abstract: Grazing cover crops (CC) could provide an economic incentive to increase adoption rates in the southeastern United States. However, understanding grazing effects on soil properties is lacking for most soils of the region. Effects of grazing or rolling a cereal rye (Secale cereale L.) CC prior to no-till planting cotton (Gossypium hirsutum L.) were determined in 2009 after 4 yr on Cecil soil, in the Southern Piedmont near Watkinsville, GA. The four catchments had a previous long history of no-till cropping with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Of 11 studies evaluating impacts of cover crop or annual forage grazing, six studies reported increases in bulk density in the upper 10 cm (Bonetti et al., 2019; Franzluebbers & Stuedemann, 2008; George et al., 2013; Kelly et al., 2021; Tobin et al., 2020; Tollner et al., 1990), with the remaining five reporting no effect (Anderson et al., 2021; Blanco‐Canqui et al., 2020; Dhaliwal & Kumar, 2021; Hill et al., 2004; Simon et al., 2021). Of 10 studies reporting penetration resistance, five reported increases (Dhakal et al., 2022; Franzluebbers & Stuedemann, 2008; Mullins & Burmester, 1997; Schomberg et al., 2021; Tollner et al., 1990) and four reported no effect (Anderson et al., 2021; Blanco‐Canqui et al., 2020; Crowell et al., 2021; Dhaliwal & Kumar et al., 2021; Tracy & Zhang, 2008). It is also important to note that the majority of these studies did not report increases in bulk density or penetration resistance that would be expected to limit root penetration and thus impact crop production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 11 studies evaluating impacts of cover crop or annual forage grazing, six studies reported increases in bulk density in the upper 10 cm (Bonetti et al., 2019; Franzluebbers & Stuedemann, 2008; George et al., 2013; Kelly et al., 2021; Tobin et al., 2020; Tollner et al., 1990), with the remaining five reporting no effect (Anderson et al., 2021; Blanco‐Canqui et al., 2020; Dhaliwal & Kumar, 2021; Hill et al., 2004; Simon et al., 2021). Of 10 studies reporting penetration resistance, five reported increases (Dhakal et al., 2022; Franzluebbers & Stuedemann, 2008; Mullins & Burmester, 1997; Schomberg et al., 2021; Tollner et al., 1990) and four reported no effect (Anderson et al., 2021; Blanco‐Canqui et al., 2020; Crowell et al., 2021; Dhaliwal & Kumar et al., 2021; Tracy & Zhang, 2008). It is also important to note that the majority of these studies did not report increases in bulk density or penetration resistance that would be expected to limit root penetration and thus impact crop production.…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to note that the majority of these studies did not report increases in bulk density or penetration resistance that would be expected to limit root penetration and thus impact crop production. The exception appears to be when cattle graze cover crop under wet soil conditions (Schomberg et al., 2021). However, even in this situation the increase appeared to be short lived with limited impact on crop yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grazing CCs can alleviate some of the economic concerns of adopting CCs (Bergtold et al., 2017; Holman et al., 2022; Schomberg et al., 2021). Studies from different regions in the United States including Alabama (Siri‐Prieto et al., 2007b), Georgia (Franzluebbers & Stuedemann, 2007; Schomberg et al., 2014), and South Dakota (Tobin et al., 2020) reported that grazing CCs can generate between $100 and $260 ha −1 greater return than non‐grazed CCs.…”
Section: Grazing Cover Crops and Economicsmentioning
confidence: 99%
“…Greenwood and McKenzie (2001) reported that water infiltration is one of the most sensitive soil properties of animal grazing due to its dependence on soil porosity. It is thought that grazing CCs could reduce the opportunity time for water infiltration and thus increase runoff potential by removing CC residues and reducing the surface protective cover (Schomberg et al., 2021). Reduced surface cover can lead to surface sealing and closure of surface‐connected macropores.…”
Section: Impacts Of Grazing Cover Crop On Soil Propertiesmentioning
confidence: 99%